Transcriptional analysis of adipose tissue during development reveals depot-specific responsiveness to maternal dietary supplementation - Fainberg, Hernan P.; Birtwistle, Mark; Alagal, Reham; Alhaddad, Ahmad; Pope, Mark; Davies, Graeme; Woods, Rachel; Castellanos, Marcos; May, Sean T.; Ortori, Catharine A.; Barrett, David A.; Perry, Viv; et al. (Nature Publishing Group, 2018)
Brown adipose tissue (BAT) undergoes pronounced changes after birth coincident with the loss of the BAT-specifc uncoupling protein (UCP)1 and rapid fat growth. The extent to which this adaptation may vary between anatomical locations remains unknown, or whether the process is sensitive to maternal dietary supplementation. We, therefore, conducted a data mining based study on the major fat depots (i.e. epicardial, perirenal, sternal (which possess UCP1 at 7 days), subcutaneous and omental) (that do not possess UCP1) of young sheep during the frst month of life. Initially we determined what effect adding 3% canola oil to the maternal diet has on mitochondrial protein abundance in those depots which possessed UCP1. This demonstrated that maternal dietary supplementation delayed the loss of mitochondrial proteins, with the amount of cytochrome C actually being increased. Using machine learning algorithms followed by weighted gene co-expression network analysis, we demonstrated that each depot could be segregated into a unique and concise set of modules containing co-expressed genes involved in adipose function. Finally using lipidomic analysis following the maternal dietary intervention, we confrmed the perirenal depot to be most responsive. These insights point at new research avenues for examining interventions to modulate fat development in early life.